2021
DOI: 10.4103/ijcm.ijcm_239_20
|View full text |Cite
|
Sign up to set email alerts
|

Are village health, sanitation, and nutrition committees functional? Evidence from Chhattisgarh and Madhya Pradesh

Abstract: Background: The Village Health, Sanitation, and Nutrition Committee (VHSNC) is a participatory effort aimed to strengthen the village-level agencies and to provide better health and sanitation services. However, there is a lack of evidence on the functionality of VHSNCs. Objectives: The present study aimed to explore the functionality of VHSNCs in the selected localities. Materials and Methods: The study was conducted in five districts of Chh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, several studies have reported that VHSNCs do not have the required number of members among them for proper functioning. Azeez et al 9 noted that <10 members were present in ~17 per cent of the committees. Srivastava et al 10 reported that VHSNCs were formed according to the State-level guidelines in both Jharkhand and Odisha.…”
Section: Village Health Sanitation and Nutrition Committees (Vhsncs):...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, several studies have reported that VHSNCs do not have the required number of members among them for proper functioning. Azeez et al 9 noted that <10 members were present in ~17 per cent of the committees. Srivastava et al 10 reported that VHSNCs were formed according to the State-level guidelines in both Jharkhand and Odisha.…”
Section: Village Health Sanitation and Nutrition Committees (Vhsncs):...mentioning
confidence: 99%
“…and service users like pregnant women constitute the VHSNCs 8 . The VHSNC is aimed to plan and implement health, nutrition and sanitation targets for the marginalized and poor sections at the village level 9 . Although VHSNCs are envisioned to ensure community participation, their performances are also influenced by the factors such as accessibility of funds and preparedness of their members to perform.…”
Section: Village Health Sanitation and Nutrition Committees (Vhsncs):...mentioning
confidence: 99%
See 2 more Smart Citations
“…It oversees the operation of the village's Anganwadi Center (AWC) and supports its efforts to raise the nutritional status of mothers and children. 21…”
Section: Village Health Sanitation and Nutrition Committee (Vhsnc)mentioning
confidence: 99%